2000
DOI: 10.2460/ajvr.2000.61.430
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary potassium citrate supplementation on urine pH and urinary relative supersaturation of calcium oxalate and struvite in healthy dogs

Abstract: Dietary potassium citrate supplementation has limited effects on urinary variables in most healthy dogs, although supplementation results in maintenance of a higher urine pH later in the day. Consequently, if supplementation is introduced, dogs should be fed twice daily and potassium citrate should be given with both meals or with the evening meal only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 18 publications
0
20
0
3
Order By: Relevance
“…Rationale: Oral administration of granular potassium citrate (150 mg/kg/d) was associated with variable increased urinary citrate concentration (3 ± 9 mmol/L) compared to a noncitrate control (0.1 ± 0.06 mmol/L) . This result may have occurred because the optimal dose of citrate has yet to be determined.…”
Section: Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Rationale: Oral administration of granular potassium citrate (150 mg/kg/d) was associated with variable increased urinary citrate concentration (3 ± 9 mmol/L) compared to a noncitrate control (0.1 ± 0.06 mmol/L) . This result may have occurred because the optimal dose of citrate has yet to be determined.…”
Section: Partmentioning
confidence: 99%
“…Rationale: Oral administration of granular potassium citrate (150 mg/kg/d) was associated with variable increased urinary citrate concentration (3 AE 9 mmol/L) compared to a noncitrate control (0.1 AE 0.06 mmol/ L). 67 This result may have occurred because the optimal dose of citrate has yet to be determined. In a summary of 5 studies with 283 human calcium oxalate stone formers, 97 (34%) reformed stones or had residual stones grow; this outcome occurred in 15% of patients receiving citrate salts compared to 52% of those not receiving citrate.…”
Section: Recommendation 31: Prevent Sterile Struvite Uroliths By Feementioning
confidence: 99%
“…However, there have been no studies in cats investigating the effects of dietary citrate addition on citrate concentrations in the urine or the formation of CaOx. In healthy dogs, supplementation of dietary potassium citrate did not result in a consistent increase in urinary citrate excretion (151) . In this study, only a small, but not significant, increase in urine pH was observed.…”
Section: Urinary Citratementioning
confidence: 99%
“…, 1996). On the other hand, urine pH fluctuated widely even after dietary supplementation with potassium citrate, although 24‐h accumulated urine was successfully alkalinized (Stevenson et al. , 1998, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For urine acidification and alkalinization, dogs received 0.2 g of ammonium chloride (Kokoshchuk, 1978; Taton et al. , 1984) and 0.6 g of potassium citrate (Stevenson et al. , 2000; Fjellstedt et al.…”
Section: Methodsmentioning
confidence: 99%